Réponses

2013-06-04T13:05:20+02:00

6x-5=3x+2

6x-3x=2+5

3x=7

x=7/3

b)

-4x+11=9x-15

-4x-9x=-15-11

-13x=-26

x=-26/-13

x=+2

c)

8x+3=x+5

8x-x=5-3

7x=2

x=2/7

d)

-15x-13=-5x+3,2

-15x+5x=3,2+13

-10x=16.2

x=-16,2/10

x=-1,62

 

si d) est  :

 

-15x-13=-6x+3,2

-15x+6x=3,2+13

-9x=16,2

x=-16,2/9

x=-1,8

  • Utilisateur Brainly
2013-06-04T14:00:31+02:00

bonjour donc voila

 

1)6x-5=3x+2

6x-3x=+5+2

3x=7

x=7/3=

 

2)-4x+11=9x-15

-4x-9x=-15-11

-13x=-26

x=-26/-13x

 

3)8x+3=x+5

8x-x=+5-3

7x=2

X=2/7

 

4)-15x-13=-5x+3,2

-15x+5x=+13+3,2

-10x=16,2

x=16,2/10

 

 

 

jespere t'avoir aider :)